What Makes Generation Y Employees Embbeded in Organisation? The Role of Self-Leadership, Job Crafting and Psychological Capital - Anissa Rizka Amanda; Fajrianthi Fajrianthi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Organisations are currently faced with phenomenon of generation Y employees who easly leave the organisastion. In fact, generation Y employees still dominate the total number of employees in the organisation. Some previoes research focused on what factors cause someone to leave an organisastion, but there is still little research that focused on what factors can make someone stay in organisation. This study aims to determine the effect of self-leadership and job crafting on job embeddedness with psychological capital as a mediating variable on Y generation employees. A total of 190 generation Y employees participated in this study. This study uses the revised self-leadership questionnaire developed by Neck and Houghton (2002) with a reliability of 0,923, job crafting scale developed by Tims, Bakker dan Derks (2011) with a reliability of 0,755, psychological capital questionnaire short version developed by Luthans, et al. (2007) with a reliability of 0,876 and job embeddedness scale developed by Mitchel, et al. (2001) with a reliability of 0,867. Hypothesis testing in this research is Partial Least Square method. The result of this research show that job crafting has an influence on job embeddedness in generation Y employees, while self-leadership and psychological capital have no effect on job embeddedness in generation Y employees. The result of this research can be used as suggestion for organisations to use job crafting as a tool to make generation Y employees embbeded with organisation.Organisasi saat ini sedang dihadapkan pada fenomena karyawan generasi Y yang mudah meninggalkan organisasi. Padahal hingga saat ini karyawan generasi Y masih mendominasi dari total keseluruhan karyawan di suatu organisasi. Beberapa penelitian terdahulu lebih berfokus pada faktor apa yang menyebabkan seseorang meninggalkan organisasi, namun masih sedikit penelitian yang berfokus pada faktor apa yang dapat mempengaruhi seseorang untuk tetap berada di organisasi. Penelitian ini bertujuan untuk mengetahui pengaruh self-leadership dan job crafting terhadap job embeddedness dengan psychological capital sebagai variabel mediator pada karyawan generasi Y. Sebanyak 190 karyawan generasi Y berpartisipasi dalam penelitian ini. Penelitian ini menggunakan revised self-leadership questionnaire yang dikembangkan oleh Neck dan Houghton (2002) dengan reliabilitas sebesar 0,923, job crafting scale yang dikembangkan oleh Tims, Bakker dan Derks (2011) dengan reliabilitas sebesar 0,755, skala psychological capital questionnaire short version yang dikembangkan oleh Luthans, dkk. (2007) dengan reliabilitas sebesar 0,876 dan job embeddedness scale yang dikembangkan oleh Mitchel, dkk. (2001) dengan reliabilitas sebesar 0,867. Pengujian hipotesi dalam penelitian ini metode Partial Least Square. Hasil penelitian ini menunjukkan bahwa job crafting memiliki pengaruh terhadap job embeddedness pada karyawan generasi Y, sedangkan self-leadership dan psychological capital tidak berpengaruh terhadap job embeddedness karyawan generasi Y. Hasil penelitian ini dapat digunakan sebagai saran bagi prganisasi untuk menggunakan job crafting sebagai salah satu cara agar karyawan generasi Y embbeded dengan organisasi.